KKN CINTA BATIK: PELATIHAN MEMBATIK GUNA MENGEMBANGKAN KETERAMPILAN BERWIRAUSAHA REMAJA TOJO LOR - Pratama, Dian; Khanum, Wulan Ruhiyyih; Bahtiar, Bari; Muna, Rif’atul; Hasanah, Nana Nur (Jurnal Pengabdian dan Kewirausahaan, 2022)
Batik is one of Indonesia's cultures that must be preserved by the younger generation. In the midst of the Covid-19 Pandemic attacking Indonesia, KKN 62 of Airlangga University remains determined to invite and educate young people to love and preserve batik, by creating a Youth Love Batik program. This program is a batik training activity to make it an innovative product that has economic value. The target of this program is high school / vocational students in the village of Alasmalang who are on school holidays. The method used in this program is continuous training and mentoring. The results of the Youth Love Batik program are batik fabric products that are ready to be marketed, but besides batik cloth that is ready to be marketed, batiki produced from this activity is also used as material to make products that have high selling value.